Abnormal microbiota composition in the ileocolonic mucosa of Crohn's disease patients as revealed by polymerase chain reaction-denaturing gradient gel electrophoresis - Martinez-Medina, Margarita; Aldeguer, Xavier; Gonzalez-Huix, Ferran; Acero, Doroteo; Garcia-Gil, Jesús L. (Inflammatory bowel diseases, 2006)
BackgroundBacteria might play a role in the pathogenesis of Crohn's disease (CD), and patients harbor a different type and density of gut microbiota compared with normal healthy subjects. Thus, the aim of this study was to compare the microbiota adhered to the mucosa of CD patients with that of healthy subjects.MethodsPolymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) of 16S rRNA gene fragments was used to identify the dominant bacterial species present in fresh biopsy samples obtained from the mucosa of 15 healthy and 19 CD subjects. Two patients suffering from ulcerative colitis and 1 suffering from ischemic colitis also were included.ResultsIndividuals were clustered in 2 groups according to their molecular fingerprint, which differentiated the majority of CD specimens (88.2%) from the majority of healthy/ulcerative colitis/ischemic colitis specimens (82.3%). In addition, the patient-to-patient variability in microbiota was greater within the CD cluster than in the healthy/ulcerative colitis cluster (P = 0.000). One hundred forty-one sequences were obtained from the PCR-DGGE bands that were grouped into 58 different phylotypes, 8 of which were novel. BLAST analysis revealed that 74.5% of the sequences were similar to those of bacteria that have never been cultivated. In CD samples, prevalence values for Clostridium spp Ruminococcus torques and Escherichia coli were significantly higher, whereas Faecalibacterium was more frequently found in healthy specimens. Opportunistic pathogenic γ-proteobacteria were found occasionally, only in CD mucosal microbiota.ConclusionsMicrobiota attached to the ileocolonic mucosa of CD patients is distinguishable from that of healthy subjects. We postulate that individuals who are predisposed to CD are less able to regulate the microbial makeup of their intestines, which leads to an unstable microbial population.